American Indian and Alaska Native overexposure to foster care and family surveillance in the US: A quantitative overview of contemporary system contact. (June 2023) - Edwards, Frank; Rocha Beardall, Theresa; Curtis, Hannah
Abstract: Following a long history of forced assimilation through family separation, American Indian and Alaska Native (AIAN) children continue to be separated from their families by state child welfare agencies at exceptionally high rates. This study identifies those states with high levels of contemporary AIAN family separation through non-tribal state and local foster care systems. We describe how these risks vary over childhood and vary in magnitude relative to white children. We then examine three states with exceptionally high rates of AIAN foster care placement, Minnesota, Alaska, and Montana, in detail. We evaluate how child maltreatment reporting contributes to upstream inequalities in family separation through an examination of sources of maltreatment reports and types of alleged maltreatment across childhood. We conclude by arguing that child welfare scholars should understand contemporary AIAN child welfare system contact in the context of historical and ongoing settler colonialism. In order to reduce AIAN inequalities, child protective services should observe tribal sovereignty by deferring to the authority of tribes in caring for Native children and families and increasing the capacity tribes have to help their communities.